Implementasi Kebijakan Pencegahan Pemberantasan Penyalahgunaan dan Peredaran Gelap Narkotika di Badan Narkotika Nasional Kota Palu - Dewi, Adilla; mangngasing, nasir; Sri Astuti, Agusta (JPS: Journal of Publicness Studies, 2024)
This study aims to determine the Implementation of policies to prevent the eradication of drugabuse and illicit trafficking in the Palu City National Narcotics Agency. The research method usedis Descriptive Qualitative, namely providing an overview of the phenomenon or focus of theproblem being researched which occurred at the research location according to existing facts. Thedata collection techniques used were observation, in-depth informant interviews anddocumentation to collect the required data in the form of primary and secondary data. Meanwhile,there were 5 informants in this research, namely 4 from the Palu City National Narcotics Agency(BNN) and 1 drug user in Palu City. The theory used in this study is George C. Edward III's theorywhere there are four indicators used in the Implementation stages of the Prevention Policy forEradicating Narcotics Abuse and Illicit Trafficking in the Palu City National Narcotics Agency.The four indicators are Communication, Resources, Disposition and Bureaucratic Structure.Based on the results of the study, it shows that the Implementation of the policy for preventing theeradication of drug abuse and illicit trafficking in the Palu City National Narcotics Agency hasgone well on several indicators, namely Communication, Disposition and Bureaucratic Structure.Meanwhile, the Resource indicator has not gone well. This can be seen from the insufficient staffat the Palu City National Narcotics Agency (BNN), as well as the inadequate facilities andinfrastructure at the Palu City National Narcotics Agency (BNN) office. All forms of theseproblems need repair and overhaul so that they run well in the future.